5c+c+7=3c-4c+3c

Since c is on the right side of the equation, switch the sides so it is on the left side of the equation.

3c-4c+3c=5c+c+7

Subtract 4c from 3c.

-c+3c=5c+c+7

Add -c and 3c.

2c=5c+c+7

2c=5c+c+7

Add 5c and c.

2c=6c+7

Subtract 6c from both sides of the equation.

2c-6c=7

Subtract 6c from 2c.

-4c=7

-4c=7

Divide each term in -4c=7 by -4.

-4c-4=7-4

Cancel the common factor of -4.

Cancel the common factor.

-4c-4=7-4

Divide c by 1.

c=7-4

c=7-4

Move the negative in front of the fraction.

c=-74

c=-74

The result can be shown in multiple forms.

Exact Form:

c=-74

Decimal Form:

c=-1.75

Mixed Number Form:

c=-134

Solve for c 5c+c+7=3c-4c+3c